Respons Pertumbuhan dan Hasil Tanaman Cabai Merah Besar (Capsicum annuum L.) Varietas Tanjung-2 Akibat Aplikasi Kombinasi Pupuk NPK dan Pupuk Kandang Kambing pada Tanah Latosol di Kota Bogor - Erviana, Asvia; Laksono, Rommy Andhika; Syafi’i, Muhammad (Indonesian Journal of Agrotech, 2023)
The obstacles in the cultivation of large chili include factors of less fertile soils so that production is not optimal, it is necessary to improve the soil by fertilizing. The fertilizesr used are required to be easy to obtain and efficient. The purpose of this research is to get the obtain a combination of goat manure fertilizer and NPK fertilizer doses that gives the highest result of large chili Tanjung-2 varieties in Bogor City. This research was conducted in Kiara Residence, Curug Village, West Bogor, Bogor City with from August, 2021 to January, 2022. The research used an experimental method using a single factor Randomized Block Design (RBD) consisting of 10 treatments in 3 replications: A(without fertilizer), B (5tons/ha manure fertilizer+250kg/ha NPK), C (10tons/ha manure fertilizer+250kg/ha NPK), D (15tons/ha manure fertilizer+250kg/ha NPK), E (5tons/ha manure fertilizer+500kg/ha NPK), F (10tons/ha manure fertilizer+500kg/ha NPK), G (15tons/ha manure fertilizer+500kg/ha NPK), H (5tons/ha manure fertilizer+750kg/ha NPK), I (10tons/ha manure fertilizer+750kg/ha NPK) and J (15tons/ha manure fertilizer+750 kg/ha NPK). The results of this study were significantly different effects on the average plant height, stem diameter, number of leaves, number of fruits, fresh weight of fruit per plant, fresh weight of fruit per plot and fruit diameter. Goat manure fertilizer 15 tons/ha and NPK fertilizer 750 kg/ha was able to provide the highest fresh weight of fruit of 5,30 tons per hektar (in three harvestings).